Aktivitas Sitotoksik Ekstrak Keong Laut Matah Merah (Cerithidea obtusa) terhadap Sel Kanker Kolon WiDr - Dewa, Wisnu Jaka; Handharyani, Ekowati; Purwaningsih, Sri; Mariya, Silmi (Jurnal Sain Veteriner, 2024)
Based on data released by Globocan in 2020, the incidence of colorectal cancer is the fourth highest in Indonesia (8.6%) and the third in the world (10%). This disease is hard to treat because the available therapy is less effective. Therefore, it is necessary to develop effective alternative therapies, especially those originating from Indonesia's natural resources, easy to obtain and reproduce. This study aims to determine the potential of red eye snail extract as an anticancer through cytotoxicity tests with the MTT Assay method on colon cancer cells WiDr and DNA fragmentation tests with Hoescth staining. In this study, we used various concentrations of the red-eye snail extract to test with 3-(4,5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide (MTT) and doxorubicin reagents as positive controls. Absorbance values were read using a microplate reader at a wavelength of 595 nm. The cell absorbance data was converted into cell viability and probit analyzed to obtain the IC50 value. The results showed that the higher the concentration of the extract caused a decrease in the number of WiDr cells and an increase in damage to the structure of WiDr cells. Based on the results of probit analysis, it was found that the IC50 value of the extract was 36.28 µg/mL or classified as moderate cytotoxicity. The DNA fragmentation test showed that at concentrations of 125 ppm and 62.5 ppm, it was able to provide an effect similar to doxorubicin, namely triggering apoptosis in WiDr colon cancer cells.